2009
DOI: 10.1111/j.1742-7843.2008.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Properties of the Hydroalcoholic Extract and the Flavonoid Rutin Obtained from Polygala paniculata L. in Mice

Abstract: The present study examined the antinociceptive effects of a hydroalcoholic extract of Polygala paniculata in chemical and thermal behavioural models of pain in mice. The antinociceptive effects of hydroalcoholic extract was evaluated in chemical (acetic-acid, formalin, capsaicin, cinnamaldehyde and glutamate tests) and thermal (tail-flick and hot-plate test) models of pain or by biting behaviour following intratecal administration of both ionotropic and metabotropic agonists of excitatory amino acids receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 36 publications
2
25
0
5
Order By: Relevance
“…For instance, rutin decreased paw edema induced by carrageenan and arthritis induced by adjuvant plus carrageenan in rats (Guardia et al, 2001;Rotelli et al, 2003). It also reduced nociception induced by glutamate in mice paws (Lapa et al, 2009), renal inflammation induced by cysplatin in rats (Arjumand et al, 2011) and cystitis induced by cyclophosphamide in mice (Boeira et al, 2011). These studies reinforce the possibility of rutin's role in the effects observed in CBDO-induced pancreatitis in rats.…”
Section: Discussionsupporting
confidence: 51%
“…For instance, rutin decreased paw edema induced by carrageenan and arthritis induced by adjuvant plus carrageenan in rats (Guardia et al, 2001;Rotelli et al, 2003). It also reduced nociception induced by glutamate in mice paws (Lapa et al, 2009), renal inflammation induced by cysplatin in rats (Arjumand et al, 2011) and cystitis induced by cyclophosphamide in mice (Boeira et al, 2011). These studies reinforce the possibility of rutin's role in the effects observed in CBDO-induced pancreatitis in rats.…”
Section: Discussionsupporting
confidence: 51%
“…Both compounds were active in chemical nociceptive models used in this work, but with less activity than the whole extract. The phytochemical analysis showed that other compounds are present in the aqueous extract and they could contribute to the analgesic activity of the extract, since the antinociceptive activity of chlorogenic acid, caffeic acid, gallic acid, isoquercetin and rutin has previously reported (De Campos Buzzi et al, 2009;Dos Santos et al, 2006;Gorzalczany et al, 2011b;Krogh et al, 2000;Lapa et al, 2009). In accordance with our results, Leal et al (2011) showed antinociceptive properties induced by vanillic acid in the formalin test and compounds with similar chemical structure, such as vanillin also possess an antinociceptive profile (Park et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Aerial part Asthma Treatment Antidepressant (Bettio et al, 2011), antifungal (Johann et al, 2011), antinociceptive (Lapa et al 2009), antioxidant (Silva et al 2005), antiprotozoal , gastroprotective (Lapa et al 2007), vasorelaxant and hypotensive (Lapa et al 2011 Anticancer (Adebayo et al, 2010), antioxidant (Adebayo et al, 2010), antiprotozoal (Nour et al, 2010), analgesic, antipyretic and anti-inflammatory, anticoagulation, antimicrobial, anticonvulsant, chronic pain in osteoarthrotic patients, and neuromuscular blocking (Okunade, 2002). JCJ85…”
Section: Polygalaceaementioning
confidence: 98%